Knowledge about Reproductive Health among Students in Junior High School 3 Keruak, East Lombok - Intan Farida Yasmin; Dicky Adi Putra; Sayyid Abdil Hakam; Lia Fristka; Jimmi Lihartanadi; Matt Biondi; Christiani Christiani; Ayu Kartika Sari; Alain Laurent (Lembaga Penelitian Universitas YARSI, 2020)
Aims: The study aimed to analyze the knowledge level on reproductive health among junior high school students in a rural district, Keruak, East Lombok. Methods: A cross-sectional, descriptive study was carried out among seventh and eighth-grade students (n=139) in Junior High School 3 Keruak, East Lombok, from March to April 2015. All participants answered a validated questionnaire consisting of 66 questions regarding reproductive health, STIs (sexually transmitted infections), and HIV-AIDS. Results: The students had low scores in all three topics. They obtained the highest score on a reproductive health topic and the lowest score on STIs topic. Students in the eighth grade had a better score in reproductive health and HIV-AIDS than those in the seventh grade. Male students had better knowledge of reproductive health and HIV-AIDS than female students (p